2012
DOI: 10.4088/jcp.11m07564
|View full text |Cite
|
Sign up to set email alerts
|

Exposure Therapy,d-Cycloserine, and Functional Magnetic Resonance Imaging in Patients With Snake Phobia

Abstract: ClinicalTrials.gov identifier: NCT01450306.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 51 publications
0
33
2
Order By: Relevance
“…A cellular target of particular interest is the N-methyl-D-aspartate (NMDA) glutamate receptor, which supports the process of long-term synaptic potentiation thought to underlie the new associative learning that occurs during extinction (Orsini & Maren 2012; Myers and Davis 2007). Indeed, a large body of literature indicates that administration of the partial NMDA agonist D-cycloserine (DCS) in conjunction with exposure therapy facilitates reductions in abnormal fear and anxiety in human clinical populations (Difede, et al, 2013; Ressler et al, 2004; Hoffmann et al, 2006; Guastella, Richardson et al, 2008; Nave et al, 2012). Early findings in rodents have also demonstrated that DCS can facilitate extinction when administered before or after exposure to fearful cues (Walker, Ressler, Lu & Davis 2002; Ledgerwood, Richardson, Cranney 2003), reduce the reinstatement of fear (Ledgerwood, Richardson, and Cranney 2004), and aid the generalization of extinction to a second non-extinguished cue (Ledgerwood, Richardson and Cranney 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A cellular target of particular interest is the N-methyl-D-aspartate (NMDA) glutamate receptor, which supports the process of long-term synaptic potentiation thought to underlie the new associative learning that occurs during extinction (Orsini & Maren 2012; Myers and Davis 2007). Indeed, a large body of literature indicates that administration of the partial NMDA agonist D-cycloserine (DCS) in conjunction with exposure therapy facilitates reductions in abnormal fear and anxiety in human clinical populations (Difede, et al, 2013; Ressler et al, 2004; Hoffmann et al, 2006; Guastella, Richardson et al, 2008; Nave et al, 2012). Early findings in rodents have also demonstrated that DCS can facilitate extinction when administered before or after exposure to fearful cues (Walker, Ressler, Lu & Davis 2002; Ledgerwood, Richardson, Cranney 2003), reduce the reinstatement of fear (Ledgerwood, Richardson, and Cranney 2004), and aid the generalization of extinction to a second non-extinguished cue (Ledgerwood, Richardson and Cranney 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, participants receiving DCS-augmented exposures also exhibited expedited treatment gains relative to placebo [32]. Similar findings for an expedited therapeutic benefit were observed among DCS-enhanced exposures for ophidiophobia (fear of snakes) as evidenced by shorter time to complete a 13-step exposure hierarchy [36], as well as enhanced therapeutic outcome after DCS-augmented subliminal exposures for sub-threshold arachnophobia (fear of spiders) as evidenced by a significantly lower rating of disgust [35]. Countering these findings, Guastella et al [34] found no enhanced benefit of DCS-augmented exposures among individuals with sub-threshold arachnophobia.…”
Section: Introductionmentioning
confidence: 81%
“…Translated into a therapeutic context, these findings suggest that learned fear memories can be updated with new information during specific time periods that can allow practitioners to maximize the therapeutic effects of exposure-based treatments. Randomized controlled trials have examined the benefit of DCS-augmented exposure-based treatment across specific phobias (e.g., acrophobia [32,33], arachnophobia [34,35], ophidiophobia [36]), PD [37,38], SAD [3942], OCD [4348], and PTSD [4952]. Table 1 presents the characteristics and findings from RCTs that have evaluated DCS in the context of exposure-based interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In SAD, two randomized, double-blind, placebo-controlled trials suggest that DCS (50 mg) administered adjunctively to exposure therapy is associated with beneficial effects in reducing symptom severity, altering dysfunctional cognitions and reducing overall impairment [70,71]. In individuals with specific phobia, augmentation of exposure therapy with DCS (50 mg) was found to lead to changes in prefrontal (especially ventromedial) cortex response to phobic stimuli [72], but these findings may not necessarily translate to patients with SAD.…”
Section: Potential Novel Pharmacological Treatmentsmentioning
confidence: 99%